Saccharomyces boulardii ameliorates clarithromycin- and methotrexate-induced intestinal and hepatic injury in rats - (:unkn) unknown (CAMBRIDGE UNIV PRESS, 2013)
Saccharomyces boulardii is a probiotic used for the prevention of antibiotic-associated diarrhoea. We aimed to investigate whether S. boulardii could alter the effects of clarithromycin (CLA) and methotrexate (MTX) on oro-caecal intestinal transit and oxidative damage in rats. Rats were divided into two groups receiving a single dose of MTX (20 mg/kg) or CLA (20 mg/kg per d) for 1 week. Groups were treated with either saline or S. boulardii (500 mg/kg) twice per d throughout the experiment. The control group was administered only saline. Following decapitation, intestinal transit and inflammation markers of glutathione (GSH), malondialdehyde and myeloperoxidase were measured in intestinal and hepatic tissues. CLA and MTX increased intestinal transit, while S. boulardii treatment slowed down CLA-facilitated transit back to control level. Both MTX and CLA increased lipid peroxidation while depleting the antioxidant GSH content in the hepatic and ileal tissues. Conversely, lipid peroxidation was depressed and GSH levels were increased in the ileal and hepatic tissues of S. boulardii-treated rats. Increased ileal neutrophil infiltration due to MTX and CLA treatments was also reduced by S. boulardii treatment. Histological analysis supported that S. boulardii protected intestinal tissues against the inflammatory effects of both agents. These findings suggest that S. boulardii ameliorates intestinal injury and the accompanying hepatic inflammation by supporting the antioxidant state of the tissues and by inhibiting the recruitment of neutrophils. Moreover, a preventive effect on MTX-induced toxicity is a novel finding of S. boulardii, proposing it as an adjunct to chemotherapy regimens.
Keywords: Saccharomyces boulardii; Clarithromycin; Methotrexate; Intestinal toxicity; Hepatic toxicity; ANTIBIOTIC-ASSOCIATED DIARRHEA; BACTERIAL TRANSLOCATION; INDUCED ENTERITIS; IN-VITRO; CELLS; INFLAMMATION; PATHOGENESIS; METAANALYSIS; GLUTATHIONE; PREVENTION